Os instrumentos do trabalho rural como testemunhos da modernização agrícola e do desenvolvimento socioeconômico do estado de São Paulo - Silva, Joana Casturina da (2011)
The record of the memory of a time is an invaluable asset that can help us understand the past be aware of this and outline prospects for the future. But little is said about the memory of the technologies, doing agricultural or farming practices such as memory space. Thus, the purpose of this study is based on the search and systematization of records of agricultural modernization in the State of Sao Paulo and its impact on socioeconomic development, therefore raising the rescue of the memory usage of agricultural equipment, such as animal traction and tractor. The survey attempted to compare the use of animal traction and mechanization in 1960 and 2007/2008, according to agricultural census prepared by IBGE and the LUPA project, the Secretary of Agriculture of the State of São Paulo, being the last survey agriculture in the country. The aim of this research was to show that over the decades, preserving the use of animal traction technique has not received the attention and is not registering memory spaces in Brazil, nor the State of São Paulo, discussed in this universe research on its history, in a systemic way, year after year, allowing a comparative study. The survey noted that there is abundant literature on the study of the heritage buildings, historic farms, but nothing that represents the agricultural history in its entirety. There are specific initiatives to create spaces of memory, many of which could not ensure its implementation, for lack of replies to messages sent asking for confirmation or otherwise of the venture. The research outlined a scenario of the origin, the use of animal traction in agriculture, the emphasis in the 1980s recorded on the return of the technique encouraged, including government programs, the introduction of modernization, symbolized by the use of tractor, importance of preserving the memory for building spaces that preserve the agricultural history, with suggestion of establishment of this area in San Carlos, interior of São Paulo, where Brazilian tractor Company (CBT) produced the first fully national tractor. In this study CBT is represented with a separate topic, the importance of the company in the history of mechanization in the country. The survey also brings some attachments that help you understand which municipalities of São Paulo animal traction and tractor tire track and was used more in the years 1960 and 2007/2008.